Methotrexate-conjugated zinc oxide nanoparticles exert a substantially improved cytotoxic effect on lung cancer cells by inducing apoptosis - Mishra, Prakriti; Ali Ahmad, Mohd Faizan; Al-Keridis, Lamya Ahmed; Saeed, Mohd; Alshammari, Nawaf; Alabdallah, Nadiyah M.; Tiwari, Rohit Kumar; Ahmad, Afza; Verma, Mahima; Fatima, Shireen; Ansari, Irfan Ahmad (Frontiers in Pharmacology, 2023)
In the current study, we report the synthesis of methotrexate-conjugated zinc oxide nanoparticles (MTX-ZnONPs) and their high efficacy against lung cancer cells. Conjugation of MTX with ZnONPs was authenticated by UV-Vis spectroscopy, DLS, FTIR and TEM. The drugnanoconjugate also showed high-drug loading. The therapeutic efficacy of MTX-ZNONPs was further tested in vitro against A549 cells, and the results of the MTT and LDH release assay showed that MTX-ZnONPs as well as free MTX were efficient in exerting cytotoxic effect in A549 cells; however, the effectiveness of MTX-ZnONPs was found to be considerably enhanced at very low doses when compared to free MTX. Moreover, ZnONPs alone significantly inhibited the cell viability of A549 cells at a much higher concentration as compared to MTX-ZnONPs as well as MTX. Furthermore, the cytomorphology of A549 cells was characterised by cellular shrinkage and detachment from the surface in all treatment groups. Similarly, A549 cells, among all the treatment groups, showed fragmented and condensed nuclei, indicating the initiation of apoptosis.Mitochondrial membrane potential (ψm) in A549 cells showed a gradual loss among all the treatment groups. Results of the qualitative and quantitative analysis depicted increased reactive oxygen species (ROS) level in A549 cells. The results of the caspase activity assay showed that MTX-ZnONPs as well as free MTX caused significant activation of caspase-9, -8, and -3 in A549 cells; however, the effect of MTX-ZnONPs was more profound at very low doses when compared to free MTX. Thus, our results showed high efficacy of MTX-ZnONPs which suggested efficient intracellular delivery of the drug by zinc oxide nanoparticles as nanocarrier.